Challenges and prospects in the telemetry of insects - Daniel Kissling, W.; Pattemore, David E.; Hagen, Melanie (Biological reviews of the Cambridge Philosophical Society, 2014)
ABSTRACT Radio telemetry has been widely used to study the space use and movement behaviour of vertebrates, but transmitter sizes have only recently become small enough to allow tracking of insects under natural field conditions. Here, we review the available literature on insect telemetry using active (battery‐powered) radio transmitters and compare this technology to harmonic radar and radio frequency identification (RFID) which use passive tags (i.e. without a battery). The first radio telemetry studies with insects were published in the late 1980s, and subsequent studies have addressed aspects of insect ecology, behaviour and evolution. Most insect telemetry studies have focused on habitat use and movement, including quantification of movement paths, home range sizes, habitat selection, and movement distances. Fewer studies have addressed foraging behaviour, activity patterns, migratory strategies, or evolutionary aspects. The majority of radio telemetry studies have been conducted outside the tropics, usually with beetles (Coleoptera) and crickets (Orthoptera), but bees (Hymenoptera), dobsonflies (Megaloptera), and dragonflies (Odonata) have also been radio‐tracked. In contrast to the active transmitters used in radio telemetry, the much lower weight of harmonic radar and RFID tags allows them to be used with a broader range of insect taxa. However, the fixed detection zone of a stationary radar unit (< 1 km diameter) and the restricted detection distance of RFID tags (usually < 1–5 m) constitute major constraints of these technologies compared to radio telemetry. Most of the active transmitters in radio telemetry have been applied to insects with a body mass exceeding 1 g, but smaller species in the range 0.2–0.5 g (e.g. bumblebees and orchid bees) have now also been tracked. Current challenges of radio‐tracking insects in the field are related to the constraints of a small transmitter, including short battery life (7–21 days), limited tracking range on the ground (100–500 m), and a transmitter weight that sometimes approaches the weight of a given insect (the ratio of tag mass to body mass varies from 2 to 100%). The attachment of radio transmitters may constrain insect behaviour and incur significant energetic costs, but few studies have addressed this in detail. Future radio telemetry studies should address (i) a larger number of species from different insect families and functional groups, (ii) a better coverage of tropical regions, (iii) intraspecific variability between sexes, ages, castes, and individuals, and (iv) a larger tracking range via aerial surveys with helicopters and aeroplanes equipped with external antennae. Furthermore, field and laboratory studies, including observational and experimental approaches as well as theoretical modelling, could help to clarify the behavioural and energetic consequences of transmitter attachment. Finally, the development of commercially available systems for automated tracking and potential future options of insect telemetry from space will provide exciting new avenues for quantifying movement and space use of insects from local to global spatial scales.